2013
DOI: 10.1021/ja4106545
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Left- and Right-Handed Molecular Screws

Abstract: Stereoselectivity is a hallmark of biomolecular processes from catalysis to self-assembly, which predominantly occur between homochiral species. However, both homochiral and heterochiral complexes of synthetic polypeptides have been observed where stereoselectivity hinges on details of intermolecular interactions. This raises the question whether general rules governing stereoselectivity exist. A geometric ridges-in-grooves model of interacting helices indicates that heterochiral associations should generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 31 publications
2
51
0
Order By: Relevance
“…Moreover, other very recent, intriguing results will greatly stimulate additional research in the fundamental field (chiral helix···helix interactions) of biomolecular processes. They include (i) stereoselectivity of the self‐assembly of left‐handed and right‐handed peptide screws with generation of novel collagen triple helix mimetics, using (Pro‐Pro‐Gly) 10 enantiomeric sequences as minimal building blocks ; (ii) polymorphism complexity (twist, chirality, and handedness inversion) exhibited by self‐aggregated peptides resulting in amyloid fibrils ; and (iii) preferred handedness of helical foldamers induced upon interaction with a protein surface .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other very recent, intriguing results will greatly stimulate additional research in the fundamental field (chiral helix···helix interactions) of biomolecular processes. They include (i) stereoselectivity of the self‐assembly of left‐handed and right‐handed peptide screws with generation of novel collagen triple helix mimetics, using (Pro‐Pro‐Gly) 10 enantiomeric sequences as minimal building blocks ; (ii) polymorphism complexity (twist, chirality, and handedness inversion) exhibited by self‐aggregated peptides resulting in amyloid fibrils ; and (iii) preferred handedness of helical foldamers induced upon interaction with a protein surface .…”
Section: Discussionmentioning
confidence: 99%
“…mixing fibril-forming L-and D peptides leads to preferential formation of heterochiral β-sheet assemblies (19). The 30-mer peptide (L-Pro-L-Pro-Gly) 10 forms a collagen-like triple helix that is very soluble in aqueous solution, but Nanda and co-workers have found that mixing solutions of enantiomeric triple helices leads to a supramolecular assembly/precipitation process that apparently involves intimate interactions between enantiomeric trimers (20). None of these intriguing studies has provided atomic-resolution insight on heterochiral associations.…”
mentioning
confidence: 99%
“…For instance, bottom‐up assembly has been demonstrated for a number of collagen peptide triple helices . These higher order assemblies have relied on cysteine knots, aromatic and electrostatic interactions, stereochemistry and shape complementarity, and metal‐ligand complexation to promote assembly beyond the triple helix. In this way, a wide range of collagen peptide‐based materials have been generated, including fibrils, sheets, and three‐dimensional matrices.…”
Section: Introductionmentioning
confidence: 99%